PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEl) PERIODE 2015-2019 - Miftahuddin, Muhammad Farhan; Sadikin, Dikdik Saleh (Journal of Accounting, Management and Islamic Economics, 2025)
This year the whole world is facing the COVID-19 pandemic, which has an impact on all companies, one of which is banking companies in Indonesia. During this pandemic, companies experienced a decline in their financial performance. However, Prior to the COVID-19 pandemic, the financial performance of banking companies in Indonesia experienced an increase. This study aims to analyze the effect of financial performance and Corporate Social Responsibility on firm value. The sample in this study was selected using a purposive sampling method so that there are 34 banking companies listed on the Indonesia Stock Exchange (IDX) used in this study. The variables used in this study are Return on Assets. Economic Value Added, Non-performing Loans, and Corporate Social Responsibility. The results in this study indicate that Economic Value added and Corporate Social Responsibility have positive and negative effects, while Return on Assets and Non-Performing Loans have no effect on Firm Value.